HUBUNGAN ANTARA KECANDUAN GAWAI (SMARTPHONE) DENGAN EMPATI MAHASISWA KEDOKTERAN UNIVERSITAS BAITURRAHMAH PADANG - Anissa , Mutiara; Azzahra , Mutia Fatimah; Triyana , Rahma; Akbar , Resti Rahmadika (MSJ : Majority Science Journal, 2023)
Background: The increasing prevalence of device addiction allows individuals to have low social skills. Empathy is a social skill that must be possessed by medical students as prospective doctors in order to create a good relationship between doctors and patients. Research on the relationship between gadget addiction and empathy in medical students is still limited. Objective: This research aims to find out whether there is a relationship between gadget addiction and empathy in students at the Faculty of Medicine, Medical Education Study Program, Baiturrahmah University, Padang class 2019-2021. Method: This research uses observational analytical methods with a cross sectional design. The population in this study were students from the Faculty of Medicine, Baiturrahmah University Medical Education Study Program in the city of Padang, class 2019-2021, who were taken using the proportionate stratified random sampling formula. The measuring instruments in this study used the Smartphone Addiction Scale - Short Version (SAS-SV) questionnaire, and the empathy questionnaire. The data analysis used is univariant data analysis presented in the form of frequency distribution, percent and bivariate analysis using the Spearman rho test. Results: Students at the Faculty of Medicine, Baiturrahmah University experienced a high level of addiction to devices (smartphones) with a high risk of 94 students (57%) and most were found in the class of 2021, namely 38 students (69%). The level of empathy obtained in this study was 151 people (91.5%) and there was a significant relationship between device addiction and empathy level. Conclusion: Based on the results of this study, it was found that there was a relationship between device addiction and empathy (r= -0.180; p= 0.021). These results show that the higher the device addiction, the lower the level of empathy.